Highly Selective Catalytic Spectrophotometric Determination of Copper in Water Samples - BAGHERI*, H.; TABATABAEE, M.; KERDEGARI, A.A.; SHAHVAZIAN†, M.; SHISHEHBORE, M.R. (Asian Journal of Chemistry, 2009)
A simple, rapid and sensitive method has been developed for determination of trace amounts of copper(II) (1-160 ng mL-1) based on it's catalytic effect on the oxidation of thionine by hydrogen peroxide in an alkaline media and in the presence of o-phenanthroline as an activator. The reaction is monitored spectrophotometrically by measuring the decrease in absorbance of thionine at 600 nm by the fixed time method. The detection limit is 0.7 ng mL-1 and relative standard deviation for ten replicate determinations of 2, 20, 50 and 100 ng mL-1 copper were 1.71, 1.2, 0.98 and 0.75 %, respectively. The proposed method is sensitive, accurate and tolerant to many foreign substances and all the reagents used are stable under the conditions. Moreover, the method is easy to perform for the determination of copper in real samples.